Effects of five nights under normobaric hypoxia on sleep quality - Hoshikawa, M.; Uchida, S.; Osawa, T.; Eguchi, K.; Arimitsu, T.; Suzuki, Y.; Kawahara, T. (Medicine & Science in Sports & Exercise, 2015)
Purpose: The purpose of this study was to evaluate the effects of five nights` sleep under normobaric hypoxia on ventilatory acclimatization and sleep quality.